CLINICAL AND IMMUNOLOGICAL FEATURES OF THE COMBINED COURSE OF PERTUSSIS AND CHLAMIDYAL INFECTION IN CHILDREN - O. P. Popova; I. M. Fedorova; S. I. Koteleva; T. A. Skirda; M. S. Blyakher; S. V. Bunin (LLC "Diagnostics and Vaccines", 2018)
The article presents the analysis of clinical and immunological features of the combined course of pertussis and respiratory chlamydia in children. The study of the prodromal period and spasmodic cough symptoms showed that concomitant chlamydial infection did not significantly affect the severity of pertussis: 63.2% of patients had mild degree and 36.8% - moderate severity of the disease. However, in this case, the disease was delayed. Bronchitis and in some cases obstructive bronchitis was observed mainly in children under 1 year.The study of the lymphocytes subpopulation found that the content of NK cells decreased only in 10.5% of children, T helpers - in 21.1%, the ratio of CD4+ /CD8+ - in 26.3%. The function of cytokine network was characterized by more active production of such proinflammatory cytokines as IFN and TNF than their production during pertussis monoinfection. The levels of production of IL-8 and IL-6 were similar in all the studied groups. The production of IL-4 by lymphocytes in children with whooping cough in combination  with chlamydial infection was weaker then in patients with pertussis monoinfection  or in healthy children. These features are considered as immunological predictors of long reconvalescence in patients with association of pertussis and respiratory chlamydia.